2019
DOI: 10.1039/c9cp04441h
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective-induced isomerization of formamide

Abstract: The new capacity of X-ray free-electron laser (XFEL) facilities to produce multi-color Xray femtosecond pulses paves the way to explore ultrafast phenomena in matter induced by X-ray photons. In the present study, we exploit the site selectivity and the high temporal resolution of a two-color X-ray femtosecond pump-probe sequence to investigate the isomerization of formamide. The pump pulse excites a particular atomic site in the molecule, while the probe pulse captures changes in the chemical environment at a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…31 Recent investigations of the sitespecificity in small molecules such as formamide, XeF 2 and acetylene dication were conducted at X-ray free-electron laser facilities using the high temporal resolution of X-ray pump-probe spectroscopy, where transient dynamics could be followed through the intermediate states. [16][17][18] Here, we have quantitatively evaluated site-specificity aspects of singly and doubly-charged photoions, by a combination of NEXAFS, coincident AES and TOF-MS. The prediction of hetero-site-specificity in species formation remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…31 Recent investigations of the sitespecificity in small molecules such as formamide, XeF 2 and acetylene dication were conducted at X-ray free-electron laser facilities using the high temporal resolution of X-ray pump-probe spectroscopy, where transient dynamics could be followed through the intermediate states. [16][17][18] Here, we have quantitatively evaluated site-specificity aspects of singly and doubly-charged photoions, by a combination of NEXAFS, coincident AES and TOF-MS. The prediction of hetero-site-specificity in species formation remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…These methods were benchmarked on other simple molecules (NH 3 , H 2 CO, CO 2 ) and are thought to be generalizable. While most time-resolved NEXAFS spectra have been used to interpret dynamics due to optical/UV excitation of valence states [26,16], NEXAFS can also provide fingerprints to follow inner-shell-initiated molecular dynamics -a discipline which is now feasible and a natural extension to x-ray pump/probe methods at XFELs [17,89,90,91,92]. Ethyl trifluoroacetate has already proven itself a model for ESCA (electron spectroscopy for chemical analysis), and, now extends its reach to advance theoretical methods to describe complex innershell photoabsorption spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the generation of soft X-ray two-colour double FEL pulses, especially attosecond/few-femtosecond double pulses (Duris et al, 2020), are atractrive and stimulated renewed interest in time-resolved XPS. Oberli et al (2019), for example, showed that the N 1s → π * transition can induce an isomerization reaction in formamide and that it is possible to observe in real time hydrogen migration by time-resolved XPS, measuring the chemical shifts with the X-ray probe pulse.…”
Section: Theoretical Proposals For Xfel Experimentsmentioning
confidence: 99%